Juglans regia and Carya illinoinensis: safety, chemical composition, and preference - BASSO, Cristiana; LARA, Daiani; BERTAGNOLLI , Silvana Maria Michelin; RICHARDS, Neila Silvia Pereira dos Santos (Food Science and Technology, 2023)
This study aimed to investigate the global scientific production of Chilean walnuts and pecans, analyze the efficiency of hygienic-sanitary treatments, compare both nuts for chemical composition and preference, perform chemical analyses of the pecan nutshell, prepare food bars with nuts and shells, and test their acceptability. Studies were consulted in the Scopus database and then directed to bibliometric analysis. Hygienic-sanitary treatments were performed by placing the nuts in the shell in hot water, cold water with hypochlorite, hot water with hypochlorite, and microwave. The proximate composition followed the official methods, and the sensorial analysis of the nuts was performed through a bilateral paired affective test. Food bars were prepared, tested by an affective acceptability test, and analyzed for chemical composition. After refining the research, we observed more publications for the walnut and its satisfactory hygienic-sanitary treatment with hot water of mesophilic aerobic bacteria, molds, yeasts, Salmonella, Escherichia coli, and mycotoxins. Regarding the physicochemical composition, the results differed significantly except for the ether extract; the untrained tasters preferred pecans. The pecan nutshell showed expressive amounts of carbohydrates and fiber, and the food bars were accepted by the tasters.